Szervezeti struktúra jellemzői spanyol labdarúgó kluboknál - Bácsné Bába, Éva (International Journal of Engineering and Management Sciences, 2016)
In Hungary the developement of sport sector needs to changes in structural scheme of sport organizations. The question is that, in the different sports areasthe association-based sports model, or the buisness-based sports model can operate effectively. Nowadays, in addition to professional successes in sporting activities, Hungarian sports entities and professional sports enterprises do consider options for the most effective operations possible, and gather good international practices in order to establish such business-based sports models in Hungary that are efficiently operable. The business side of sports is particularly apparent in professional football. On a global scale, this sport clearly demonstrates the process of structural transformation that is directed at the realization of the appropriate form of enterprise and structural setup. This article has been written to describe the Spanish model by example of organizational scheme of Real Madrid and Barcelona FC.